The Platform Economy: New Competition Rules — Renaissance of Antitrust Control of the Abuse of Market Power - Justus Haucap (Wirtschaftsdienst)
Abstract While digital platforms have intensifi ed competition in many markets, there is also a higher risk of market foreclosure due to the “winner takes all”-nature of these markets. Hence, there are good reasons for a strengthening of competition law, as now planned with Germany’s competition law reform. Focussing on the control of abuse of market power instead of merger control is well founded from an economic perspective, as a stricter control of abusive behaviour makes merger control less important. Strengthening merger control is difficult: While this could better address the problem of so-called killer acquisitions, it would also worsen the problem of GAFAM kill zones, which is equally relevant.